HUBUNGAN SIKAP DAN LAMA DUDUK DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PENGRAJIN TENUN ULOS - Iskandar Markus Sembiring; Novita Br Ginting Munthe; Efeni Yesti Br Tarigan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Lower Back Pain (NPB) is one of the most common Musculoskeletal disorders in work activities. The World Health Organization (WHO) says that 2% -5% of employees in industrialized countries suffer from Lower Back Pain (NPB) each year, and 15% of abstentism in the steel industry and trade industry is caused by NPB. Lower Back Pain caused by an incorrect sitting position at work is a clinical syndrome characterized by the main symptoms of pain or other feelings that are uncomfortable in the lower back region. The purpose of this study was to determine the relationship between attitude and length of sitting with complaints of low back pain in Samura Village, Kabanjahe Subdistrict, Karo District in 2019. The type and design in this study were quantitative analytical surveys with cross sectional design conducted in March - June 2019 in Samura Village, Kabanjahe Subdistrict, Karo District with a total sample of 36 people, sampling uses the total sampling method. Retrieval of research data using observations, the instrument for data retrieval in this study is the observation sheet. Bivariate analysis using Chi Square test. The results showed the average score of respondents 'sitting attitude was (58.3%), the average score of respondents' sitting time was (63.9%) and the average score of low back pain was (50.0%). Chi Square test results showed that sitting attitude p value = 0.007 and length of sitting p value = 0.037 means Ho was rejected meaning there was a relationship between attitude and length of sitting with complaints of low back pain in Samura Village, Kabanjahe District, Karo District. The results of this study are expected to pay attention to sitting staff who are ergonomic so as not to cause lower back pain.